Antioxidant Capacity Comparison of Ethanolic Extract of Soursop (Annona muricata Linn.) Leaves and Seeds as Cancer Prevention Candidate - Dyah Ayu Widyastuti; Praptining Rahayu (Biology, Medicine, & Natural Product Chemistry, 2017)
Annona muricata Linn. (soursop) is one of  tropical plants which have relatively complete chemical compounds. It has flavonoid, tannin, phytosterol, alkaloid, etc. The high antioxidant compound in soursop is believed as cancer prevention so the cancer threat in the world can be minimized. The antioxidant compound in soursop can be found not only in its fruit, but also in other parts like leaves, seeds, etc. Based on that potency, this study aimed to compare antioxidant capacity of soursop leaves and seeds, also to study about the utilization of soursop parts which is usually not used. This research began with maceration to extract leaves and seeds with 96% ethanol. Ethanolic extract of soursop leaves and seeds were then tested for antioxidant capacity with DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The result showed that antioxidant capacity of soursop leaves and seeds are 85,66875% and 39,0166, respectively. The antioxidant capacity of leaves is higher than seeds due to seed’s extraction difficulty so its antioxidant compound could not be extracted optimally. However, either leaves or seeds extract in this study are potential as antioxidant resources because there are no significant differences between antioxidant capacity of both extract.